Development of an Agricultural Mechanization Model Based on After-sales Service in Southern Africa - (:unkn) unknown (My University, 2023)
There is a plentiful of arable land in Africa and South Africa. Africa remains the region all over the world with the lowest power usage and the lowest level of agricultural mechanization (Daum and Birner 2019; Makini et al. 2020). As the development of cross-border e-commerce and economy progress, more and more Chinese farm equipment has been sold in Africa and South Africa. As of now, one of the most significant problems that trap the farmers and users in Africa and South Africa is after-sales service. However, many researchers focus on agricultural mechanization in Sub-Sahara Africa (Mrema, Kienzle, and Mpagalile 2018; Makini et al. 2020). Few academics are concentrating on the risk reduction of after-sales service of agricultural machinery in Africa and South Africa, which is largely beneficial to the sustainable agri-machinery enterprise as well as agricultural economic growth. This research aims to meet this gap mentioned above. This research aims to develop a risk reduction model of after-sales service on Chinese agricultural machinery in South Africa.The information on arable land and agricultural mechanization in Africa and South Africa will be shown in the literature review. The development process of Chinese farm machinery, the status quo of export on the farm machine as well as Chinese agricultural equipment in Africa and South Africa will be addressed in the literature review. Furthermore, the detailed knowledge of the after-sales service of agricultural machinery and risk management will also be elaborated in this part.This study's research methodology is an explanatory research method and design in which quantitative data will be collected and analyzed first, followed by qualitative data collection and analysis. The research population in this study includes staff, workers, directors, managers, CEOs as well as presidents who work at agricultural machinery enterprises. The government officials, staff, fellows, directors who research agric
Keywords: African Research